THE INFLUENCE OF SOCIAL MEDIA MARKETING AND PRODUCT QUALITY ON PURCHASE DECISIONS AMONG GLOWDERM HOUSE OF BEAUTY CONSUMERS IN MAKASSAR CITY - Adhelia Dwi Rismawani Risal; Muhammad Jufri, Andika Isma, Agus Syam, Sumiati Tahir (CV. Adiba Aisha Amira, 2025)
The purpose of this research is (1) to determine whether there is a significant influence of social media marketing on purchasing decisions among consumers of Glowderm House of Beauty. (2) To determine whether there is a significant influence of product quality on purchasing decisions among consumers of Glowderm House of Beauty. (3) To determine the significant influence of social media marketing and product quality on purchasing decisions among consumers of Glowderm House of Beauty. This study uses a quantitative method with multiple regression analysis techniques to analyze the research data using instruments in the form of questionnaires. The population in this study consisted of 2983 customers of Glowderm House of Beauty over approximately 6 months, and a sample of 97 consumers of Glowderm House of Beauty was taken using the accidental sampling technique and calculated using the Slovin formula. The results of this study indicate that: (1) There is no significant influence of social media marketing on the purchasing decisions of Glowderm House of Beauty consumers. (2) There is a significant positive influence of product quality on purchasing decisions among consumers of Glowderm House of Beauty. (3) There is a significant positive influence of social media marketing and product quality on purchasing decisions among consumers of Glowderm House of Beauty.